THE SIGNIFICANCE OF DEVELOPING THE ANALYTICAL COMPETENCES OF YOUNG EDUCATORS IN THE PRESCHOOL EDUCATION SYSTEM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article describes the theoretical and practical aspects of the methodology of analyzing educational activities in preschool educational organizations. Also, the pedagogical importance of training analysis and the necessary aspects of mastering the methodology of educational activity analysis in improving the professional analytical competences of young pedagogues have been revealed.